Influence of Hyperglycemia on Renal Function Parameters in Patients with Diabetes Mellitus. - Sharma, Anupriya (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Urea & creatinine are the parameters to diagnose functioning of the kidney. Changes in serum creatinine concentration more reliably reflect changes in GFR than do changes in serum urea concentrations. High sugar in the blood can lead to serious health problems, including heart disease and damage to the nerves and kidneys. Study aimed to analyze the effect of hyperglycemic condition on the renal function parameter like serum urea and serum creatinine. In present study a total of 33 hyperglycemic serum samples were analyzed for their urea & Creatinine for percent variation, from their reference range corresponding to blood sugar value. At blood sugar level I (130-190 mg %) the variation among Urea concentration were analyzed. Out of 33 hyperglycemic serum samples, 15 samples were found in this category. While 190-250 mg % hyperglycemic range the level of urea haven’t showed significant variation from their reference range. Out of total 13 serum samples, 1 sample showed variation from their normal range which was also around 6.16%. for higher range of sugar concentration (250 – 380 mg %) in blood serum, the urea concentration haven’t showed much deviation only one sample found to be deflected from its normal value & the % variation for these sample was observed to be 2.22%. Creatinine level speckled in the range of 91.5– 97.5% from its normal reference range. Thus study was concluded that too much sugar in the blood can lead to diverge the renal function parameter from their normal ranges and causes serious kidneys problems